(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the frequency of using Traditional Medicine in the treatment of some common diseases of people in Huong Canh town, Binh Xuyen district, Vinh Phuc province from August 2023 to August 2024 and some related factors. Methods: Cross-sectional descriptive study. Four hundred people came to the Huong Canh medical examination and Binh Xuyen hospital in Binh Xuyen district, Vinh Phuc province from August 2023 - August 2024, who were conducted to the study by answering the pre-prepared questions. Results: The proportion of participants choosing traditional medicine for medical examination and treatment was 65,0%. The rate of medical examination and treatment using traditional medicine for various diseases is: musculoskeletal diseases (76,1%), respiratory disease (64,9%), digestive diseases 66,7% and common flu (62,4%). Traditional medicine treatment methods people have used in the past year are: acupuncture (39,8%), acupressure massage (20,3%), electro-acupuncture (13,3%), suture implantation (3,0%), ear acupuncture (2,5%) and using traditional medicine (7,5%). The reason why most people choose medical examination and treatment at the local medical centers was the medical staff has good skills, and it is close to their home. The factors which related to using traditional medicine services include: age, ethnicity, economic conditions. Conclusion: The proportion of people in Huong Canh town, Binh Xuyen district, Vinh Phuc province who used traditional medicine is quite high (65%). The patients with musculoskeletal diseases have the highest rate of using traditional medicine (76,1%). The traditional medicine therapy that people use the most is acupuncture (39,8%). Some factors related to the use of traditional medicine services in the locality include: age, ethnicity, economic conditions.